2022
DOI: 10.1136/tc-2022-057332
|View full text |Cite
|
Sign up to set email alerts
|

The smoking population is not hardening in South Korea: a study using the Korea Community Health Survey from 2010 to 2018

Abstract: IntroductionThe hardening hypothesis proposes that the proportion of hardcore smokers increases when smoking prevalence declines. To evaluate whether such hardening occurs in South Korea, we examined the association between quitting behaviours, the number of cigarettes smoked per day and the proportion of hardcore smokers and smoking prevalence among local districts in South Korea.MethodsThis study used the cross-sectional data from the Korea Community Health Survey (2010–2018) to examine local district-level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
0
0
1
Order By: Relevance
“…Die Tabakindustrie hat das Konzept der "Harm Reduction" irreführend ausgenutzt und suggeriert, dass eine vollständige Nikotin-und Tabakentwöhnung nicht immer möglich oder von den Konsumenten gewünscht ist [35]. Jüngste Untersuchungen haben jedoch gezeigt, dass es keine Verhärtung des Verhaltens in der Raucherpopulation gibt, sondern im Verlauf eine Verlagerung hin zu leichteren Rauchgewohnheiten zu beobachten ist [55][56][57]. Aus den Eurobarometerdaten für 2020 geht hervor, dass mehr als 51 % der derzeitigen Raucher in der Europäischen Union versucht haben, mit dem Rauchen aufzuhören, wobei die Mehrheit der Konsumenten dies ohne Hilfsmittel getan hat [51].…”
Section: Raucherentwöhnungunclassified
“…Die Tabakindustrie hat das Konzept der "Harm Reduction" irreführend ausgenutzt und suggeriert, dass eine vollständige Nikotin-und Tabakentwöhnung nicht immer möglich oder von den Konsumenten gewünscht ist [35]. Jüngste Untersuchungen haben jedoch gezeigt, dass es keine Verhärtung des Verhaltens in der Raucherpopulation gibt, sondern im Verlauf eine Verlagerung hin zu leichteren Rauchgewohnheiten zu beobachten ist [55][56][57]. Aus den Eurobarometerdaten für 2020 geht hervor, dass mehr als 51 % der derzeitigen Raucher in der Europäischen Union versucht haben, mit dem Rauchen aufzuhören, wobei die Mehrheit der Konsumenten dies ohne Hilfsmittel getan hat [51].…”
Section: Raucherentwöhnungunclassified
“…The tobacco industry has misleadingly exploited the concept of "harm reduction", suggesting that complete nicotine and tobacco cessation is not always possible or desired by the users [35]. However, recent evidence has shown that there is no hardening of smoking populations, and instead indicates a shift towards lighter smoking patterns over time [55][56][57]. The 2020 Eurobarometer data revealed that over 51% of current smokers in the EU had attempted to quit, with the majority of users doing so without aids [51].…”
Section: Smoking Cessationmentioning
confidence: 99%